2015
DOI: 10.4012/dmj.2015-129
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and osteogenic differentiation of human mesenchymal stem cells on zirconia and titanium with different surface topography

Abstract: The purpose of this study was to elucidate behavior of human mesenchymal stem cells (hMSCs) on yttria stabilized tetragonal zirconia polycrystals (TZP) and commercial pure titanium (CpTi) with different surface topography. Mirror-polished (MS), sandblasted with 150-μm alumina (SB150) and SB150 acid-etched (SB150E) were prepared on TZP and CpTi. Proliferation, osteogenic differentiation of hMSCs was evaluated. The scanning electron microscopy showed that micro-and nano-topographies were created on both TZP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
3
34
0
2
Order By: Relevance
“…The cellular viability results obtained in our study showed that Ti grade V had the lowest percentage of cell proliferation among the test groups. These results are similar to those of previous studies regarding the presence or not of bioactive ceramics in titanium . At all times of cell culture assessment, the control group (well plates) showed the highest values of cell viability, due to the high roughness of the polystyrene based material which is proper for cell culture.…”
Section: Discussionsupporting
confidence: 90%
“…The cellular viability results obtained in our study showed that Ti grade V had the lowest percentage of cell proliferation among the test groups. These results are similar to those of previous studies regarding the presence or not of bioactive ceramics in titanium . At all times of cell culture assessment, the control group (well plates) showed the highest values of cell viability, due to the high roughness of the polystyrene based material which is proper for cell culture.…”
Section: Discussionsupporting
confidence: 90%
“…A number of animal studies have been published that outline hard and soft tissue integration of zirconia implants on the histological level and have shown promising results [29, 32, 33]. Further, cell culture studies have demonstrated that zirconia especially with a moderately rough surface is accepted by osteoblasts and integrates into bone tissue [9, 34]. Scarano et al [35] examined the bone-implant interface of machined zirconia implants at 4 weeks of healing and reported BIC values of 68.4%.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of shot blasting and acid etching is often performed on Cp-Ti implants because it reportedly accelerates osseointegration [8][9][10][11][12][13][14][15] . In vitro experiments have demonstrated that the combination promotes adhesion, proliferation, and differentiation of osteoblasts [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have demonstrated that the combination promotes adhesion, proliferation, and differentiation of osteoblasts [11][12][13][14][15] . In vivo experiments have demonstrated that it improves bone-implant contact and increases removal torque [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%